Stability of Optimal Controls for the Stationary Boussinesq Equations - Gennady Alekseev; Dmitry Tereshko (International Journal of Differential Equations)
The stationary Boussinesq equations describing the heat transfer in the viscous heat-conducting fluid under inhomogeneous Dirichlet boundary conditions for velocity and mixed boundary conditions for temperature are considered. The optimal control problems for these equations with tracking-type functionals are formulated. A local stability of the concrete control problem solutions with respect to some disturbances of both cost functionals and state equation is proved.